Development of an E-Module on Derivative Applications for Vocational High School Students - Widjajanti, Kristina; Sarosa, Moechammad; Selviana, Vuvut (Universitas Muhammadiyah Mataram, 2023)
The Covid-19 pandemic has impacted the learning process, including the learning of mathematics. This situation has caused students and teachers not always be able to interact directly, which can result in learning loss. Therefore, efforts are needed to develop learning media that allow students to learn independently and actively. This study aims to develop a Mathematics E-Module that is different from most of the modules available, where students can interact with the E-Module. The E-Module was developed using the modified Plomp development model. The results of the study show that the developed E-Module meets the level of validity with a category of very valid, as well as the practicality of the E-Module. Other findings during the testing process showed that this E-Module can increase students' active and independent engagement in understanding the concept of derivative relationships with increasing functions, decreasing functions, and maximum/minimum values. Therefore, E-Module is recommended because it is very suitable for use in learning both online and offline. E-Module with GeoGebra applet can improve vocational school students’ ability to discover concepts independently.